Predicting pKa for proteins using COSMO-RS - Andersson, Martin Peter; Jensen, Jan Halborg; Stipp, Susan Louise Svane (PeerJ, 2013)
We have used the COSMO-RS implicit solvation method to calculate the equilibrium constants, pKa, for deprotonation of the acidic residues of the ovomucoid inhibitor protein, OMTKY3. The root mean square error for comparison with experimental data is only 0.5 pH units and the maximum error 0.8 pH units. The results show that the accuracy of pKa prediction using COSMO-RS is as good for large biomolecules as it is for smaller inorganic and organic acids and that the method compares very well to previous pKa predictions of the OMTKY3 protein using Quantum Mechanics/Molecular Mechanics. Our approach works well for systems of about 1000 atoms or less, which makes it useful for small proteins as well as for investigating portions of larger proteins such as active sites in enzymes.
Keywords: Proteins; pKa; COSMO-RS; OMTKY3; Quantum mechanics; Implicit solvent; Semi-empirical methods